Emotional fluidity in chronic care - Sanjay Kalra; Suneet Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2023)
In this exploratory opinion piece, we define emotional fluidity as a state of changing emotions which influence choice of, attitudes and behaviour towards, and response to, chronic health care and therapy. This manifests clinically as changing opinions regarding suitability of modern health care, and as or varying, responses to suggestions and interventions from the health care team. Diabetes distress is an extreme example of emotional fluidity. Emotional fluidity also encompasses the variability of the health care professional’s response to emotional and medical needs of persons seeking care. This can be inter-individual or intra-individual, and can be influenced by compassion fatigue. Health care professionals should be aware of emotional fluidity, and should be able to address its negative impact, as well as amplify its positive influence. Keywords: Patient centred care, Person centred care, Psychosocial aspects.